Lateral substituted phenyl biphenylcarboxylates ‒ non-chiral analogues of ferroelectric liquid crystals. Issue 5 (8th April 2020) - Cigl, Martin; Jurok, Radek; Hampl, František; Svoboda, Jiří; Podoliak, Natalia; Novotná, Vladimíra
ABSTRACT: We report mesomorphic properties of non-chiral liquid crystalline molecules and study the effect of lateral halogen (fluoro, chloro) substitution in the molecular core and the length of terminal chains. We have prepared nine homologue series with the molecular core substituted at different positions with respect to the ester linkage group. Additionally, we have modified the length of both terminal alkyl chains (hexyl, octyl, decyl and dodecyl) symmetrically for both terminal chains. The effects of the lateral substitution and the chain length are analysed with respect of the possibility to reduce the transition temperatures and tune the properties of presented liquid crystalline molecules. Graphical abstract: